Finding AFLP markers associated to panicle weight through bulk segregant analysis - Malone, Gaspar; Marchioro, Volmir; Kopp, Mauricio Marini; Malone, Emilia (MTT, 2004)
Molecular markers are more and more a part of plant breeding routines, since they allow one to access the genetic variability present in the entire genome without the influence of the environment. However, the application of molecular techniques is limited depending upon the character that is being pursued. The great majority of agronomically important characters are controlled by many genes of small additive effects (QTLs),which are highly influenced by the environment. In the present work, an F3 population segregating for panicle weight in oat, from the cross UFRGS 14 (High panicle weight) and OR2 (low panicle weight) was conducted up to F6 under three different methods: hill, full line and spaced plants. Contrasting bulks were formed composed of plants with the average +/- one standard deviation(sd), respectively. These bulks were screened with AFLP markers to detect putative association between marker and character.Up to 145 markers have been analyzed and three presented potential use. More markers are being screened to detect associations at this/these genomic regions.
Keywords: Ka; oats; molecular markers; panicle weight